Designand Evaluationof Fixed-Dose Combination of Bi-Layer Tablets of Dolutegravir, Lamivudine and Tenofovir Disoproxil Fumarate Tablets 50 Mg/300 Mg/300 Mg - Sankaraiah, Jonna; Sharma, Neeraj; Naim, Mohd Javed (Asian Journal of Pharmaceutical Research and Development, 2023)
Objective: The purpose of this research study is to design and evaluation of bi-layer tablet as single dosage regimen against the single dose of reference listed drugs of Brand TIVICAY (dolutegravir tablets 50 mg), EPIVER®(lamivudine tablets 300 mg), and VIREAD®(tenofovir disoproxil tablets 300 mg) to treat human immunodeficiency virus (HIV-1) infections in adults and pediatric patients weighing 40kg and greater. Methods: Formulation was designed with two layers of blendthrough lamivudine and tenofovir disoproxil fumarate (layer-I) and dolutegravir(layer-II). Both layers were manufactured by using roller compaction processand wet granulation process followed by using bi-layer compression and film coating. Layer-I and II formulations were developed by using design of experiments (DOE) to match the dissolution with each branded formulation. Two level, fractional factorial (22+3) and full factorial design (23+3) by using a design expert (version 11.0) were used to evaluate the formulation variables to prepare a robust formulation forimprove the solubility of dolutegravir and improve the flowability and uniformity of lamivudine and tenofovir disoproxil fumarate. Results: Drug–excipient compatibility results revealed that mixture of active substances resulted to increase the tenofovir impurity levels compared with individual layers. Exposed to hydrolysis and oxidation resulted to significant degradation of lamivudine and increases impurity A and C and new impurities were observed. Preformulation studies indicates that flow properties of active substances observed very, very poor and designed bi-layer compression for each blend manufactured by roller compaction (lamivudine and tenofovir) and wet granulation process (dolutegravir). Fractional factorial design (22+3) were used to identify the range of croscarmellose sodium and magnesium stearateto impact on the dissolution for Layer-I and full factorial design (23+3) were used to identify the range of sodium starch glycolate, povidone and magnesium stearate to impact on the dissolution through a design expert (version 11.0). Bi-layer compression followed by coating resulted to produce the comparable dissolution results with each branded formulation. Finally, X-ray diffraction (XRD) indicates that there are no polymorphic changes for the optimized formulation and there is no interaction between the three active substances. Conclusion: Fixed–dose combination of single dosage regimen yielded consistent drug release against each branded drug to treat human immunodeficiency virus (HIV-1) infections